Pengaruh Social Media Marketing dan Influencer Marketing Terhadap Brand Awareness Produk Somethinc Di Tanjungpinang - Haryani, Dwi Septi; Nurul Sultania; Ratnasari, Sri Langgeng; Elvira, Mita; Fenny; Fauzar, Selvi (Bahtera Inovasi, 2026)
This study aims to examine the effect of social media marketing and influencer marketing on brand awareness of Somethinc products in Tanjungpinang. The research employs a quantitative method using a survey approach. The study population consists of followers of Somethinc’s TikTok account, with a sample of 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that, partially, social media marketing has a positive and significant effect on brand awareness of Somethinc products, with a tvalue of 4.197 and a significance level of < 0.001. Influencer marketing also shows a positive and significant effect on brand awareness, with a tvalue of 3.314 and a significance level of 0.001. Furthermore, the simultaneous test (F-test) reveals that social media marketing and influencer marketing jointly have a significant effect on brand awareness, with an Fvalue of 38.145 and a significance level of < 0.001. In conclusion, digital marketing strategies through TikTok social media and collaborations with credible influencers are effective in enhancing brand awareness of Somethinc products in Tanjungpinang.